Double Consciousness in Postcolonial Literature. Case Study: Frantz Fanon's The Wretched of The Earth - Rezig, Meriga, Sarah Chifa Houda (University of El-oued, 2021)
The research paper examines the issue of double consciousness in postcolonial literature. Frantz Fanon stresses the existence of such conditions of the colonized in his book The Wretched of the Earth (1961). It emphasizes that W.E.B Du Bois double consciousness is not a condition experienced only by African Americans, but also a matter of the colonized people. The work is dedicated to the wretched people of the colonial and post-colonial periods, who experience double consciousness. The case study lends itself to postcolonial theory for its direct relationship to the impact of the colonizer on the colonized. This qualitative research adopts in its three chapters the descriptive-analytical method. The findings show that the lack of reciprocal recognition between the colonizer and the colonized is the main driver of double consciousness. Fanon's work reveals that double consciousness is a condition experienced by the natives, especially among intellectuals and nationalist bourgeoisie. This study exposes that the colonized nations are subject to experiencing inner struggles between two opposed identities, one is of the colonized and the other is of the colonizer.
Keywords: colonized, colonizer, double consciousness, post-colonialism, reciprocal recognition